STUDI RENCANA DINDING PENAHAN TANAH DESA MARGOMULYO TIPE COUNTERFORTH DENGAN PERKUATAN GEOTEKSTIL KABUPATEN KUTAI KARTANEGARA - RAHAKIM PUTRA, ARI (KURVA S JURNAL MAHASISWA, 2014)
Landslide are dispalecement slope form of rock-forming material, material destruction, soil , or the mixture of materials, moving down the slopes or out. The occurrence of landslides caused by the presence of water that seep into the soil and add weight to ground. If water penetrates the soil acts as watertight sliding plane, the ground becomes slippery and soil weathering on it will move to follow the slope and of the slopes.Margomulyo village the only acces that connects the two regions spontaneous with Tenggarong city, so in case, so in case of avalanches on the road, it can cause spontaneous isolated region. Landslide that occurred on roads in the form of sliding of the road that could potentially lead to these roads cut off, so we need a swift and appropriate Â action on dealing with avalanche that happened on these road cut off, so we need a swift appropriate action in the roads.From the calculation result can be concluded that, dimensional wall high ground is 6 meters and awith of 1 meter, 1 meter thick plate with a length of 10 meters per segment review. Secure the stability of retaining wall to bolster however effect the shear, so that the necessary foundation piles with additional bracinbg to the pile group to rigidify the structure of the walls and the pile